Phosphotungstic acid as an efficient solid catalyst for intramolecular rearrangement of benzyl phenyl ether to 2-benzyl phenol - Bhure, Mahesh H.; Rode, Chandrashekhar V.; Chikate, Rajeev C.; Patwardhan, Neeraj; Patil, Shraddha (Catalysis Communications, 2007)
An heteropoly acid (phosphotungstic acid, PTA) was found to be a promising solid acid catalyst as an alternative to the conventional stoichiometric reagents for the rearrangement of benzyl phenyl ether giving 2-benzyl phenol as a major product and 4-benzyl phenol and dibenzylated phenols as side products. Catalyst was recovered from the reaction mixture and reused again without loss of activity. Based on the observed product distribution for various substrates a plausible catalytic reaction pathway has also been proposed. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: benzyl phenyl ether; Intramolecular rearrangement; Phosphotungstic acid